Applicability of the Limberg Flap: a case series - Anelise Darabas dos Santos; Douglas Haddad; Flávia Fenólio Nigro Marcelino; Luiza Vieites (Surgical & Cosmetic Dermatology, 2022)
Local flaps are an excellent option for repairing the excision of skin tumors, where the primary closure of the defect would cause aesthetic and functional impairment.The rhomboid (Limberg) flap is a simple and versatile transposition flap that can be applied widely with good cosmetic and vascularization results. The retrospective analysis of a case series using the Limberg flap to reconstruct defects resulting from tumor resections proved to be easy to perform, with excellent evolution and vascular viability.